Computational modelling of micropolar blood-based magnetised hybrid nanofluid flow over a porous curved surface in the presence of artificial bacteria - Deebani, Wejdan; Shah, Zahir; Rooman, Muhammad; Khan, Naeem Ullah; Vrinceanu, Narcisa; Shutaywi, Meshal (Frontiers in Chemistry, 2024)
This article provides a brief comparative analysis of the influence of heat creation on the micropolar blood-based unsteady magnetized hybrid nanofluid flow over a curved surface. For modelling purpose the Powell-Eyring fluid model is applied. Furthermore, the research takes into account the impacts of viscous and Joule dissipation. By investigating the behaviour of Ag, TiO 2 nanoparticles dispersed in blood, our aim is to understand the intricate phenomenon of hybridization. In accordance with the fundamental flow assumptions, a mathematical framework has been created, which has resulted in the creation of a model. After then, this model has been made dimensionless by utilizing similarity transformations. The problem of a dimensionless system has been effectively addressed using Homotopy Analysis Technique. The cylindrical surface is utilized to calculate the flow quantities, and the outcomes are visually presented using graphs and tables. Additionally, a study is conducted to evaluate skin friction and heat transfer in relation to blood flow dynamics. Heat transmission was enhanced to raise the Biot number